SELEKSI UNIT PENANGKAPAN IKAN DI KABUPATEN MAJENE PROPINSI SULAWESI BARAT - Muh. Ali Arsyad; Tasir Tasir (Buletin PSP, 2009)
The objective of this research is selecting applicable fishing method in the term of applicable fishing development for fishermen empowerment and optimally resources exploitation.  This re-search is conducted to indentify the feasible instruments of applicable fishing for improvement ba-sed on biological, technique, social and economical aspects.  The method applied in this research is survey.  In the research, comparative study is conducted to identify reliable fishing units out of number of fishing units (purse seine, payang, gill net and beach sine) based on biological, tech-nical, social and economical aspects.  The result of research shows “floating gill net” is first priority for category of biological aspect.  While technical aspect puts purse seine on its first priority, and social aspect put purse seine and beach sine on its first priority, as well as economical aspect for business efficiency criteria put purse seine on its first priority and for investment efficiency criteria put payang on its first priority.  Purse seine is the most appropriate fishing unit for first priority in development based on biological, technical and social aspect as well as economical aspect.Key words: beach seine and purse seine, gill net, payang